Applied method for production design optimization under geologic and economic uncertainties in shale gas reservoirs. (3rd April 2018) - Plaksina, Tatyana; Gildin, Eduardo
Abstract: In the last decades innovations in horizontal drilling and hydraulic fracturing enabled production of commercial quantities of natural gas from many unconventional reservoirs. Reservoir management and development strategies for shale and tight gas plays have evolved from ad hoc approaches to more rigorous strategies that involve simulation and numerical optimization in presences of multiple economic and production objectives, constraints and uncertainties. Application of an automated integrated optimization framework for placement of transverse hydraulic fracture stages along horizontal wells might increase shale gas reserves and revenue from unconventional assets even further. However, the uncertainty present in many reservoir properties and economic parameters might have tremendous effect on success or failure of an unconventional project. In this study, we assess the uncertainty in key parameters using a full factorial design of experiment and a stepwise regression analysis and combine this assessment with an optimization strategy based on a genetic algorithm to identify the effects of uncertainty on optimal production design and revenue of an unconventional project.